Inoculation of soybean seeds coated with osmoprotector in diferents soil pH's (Acta Scientiarum. Agronomy, 2018)
Inoculation with nitrogen-fixing bacteria (Bradyrhizobium) is an indispensable technology to increase the productivity of the soybean crop. The objective of this study was to evaluate the viability of the inoculation with Bradyrizobium bacteria associated with the osmoprotector coating on different pre-sowing days and the effect of different soil pH on the components of yield, nodulation and grain yield of soybean. Two soybean cultivars were used, sown in two seasons and submitted to soil pH of 5.3 and 6.5. The seeds were inoculated at different pre-sowin periods with Bradyrizobium bacteria in the presence or absence of osmoprotectants. In the cultivar NA 5909RG (pH 5.3), the seeds inoculated with Bradyrhizobium and osmoprotector, at four and seven days of pre-sowing, presented an increase of 10.8% and 8.3% of productivity, in relation to those without osmoprotector. The osmoprotector and the inoculation of Bradyrhizobium increases the number and dry mass of nodules in soil with more acidic pH. The soil of lower acidity is responsible for higher grain yield, compared to the higher acidity, when both were not inoculated. The variable with the greatest explanatory power and contribution in the variability in the data of the experiment is the grain yield.